Adoption of improved soybean and gender differential productivity and revenue impacts: Evidence from Nigeria. (6th May 2022) - Kamara, Amadu Y.; Oyinbo, Oyakhilomen; Manda, Julius; Kamsang, Lucy S.; Kamai, Nkeki
Abstract: Despite the considerable soybean varietal improvement and dissemination efforts in Nigeria and other parts of Sub‐Saharan Africa, empirical evidence on farm‐level yield and revenue impacts of improved soybean varieties (ISVs) from a gender perspective are limited. In this paper, we analyze the impact of the adoption of ISVs on soybean yield and net revenue, and the associated gender differential effects in northern Nigeria. We use the endogenous and exogenous switching treatment effects regression frameworks to estimate the impacts. We find that the adoption of ISVs significantly increased soybean yield and net revenue of the soybean‐producing households by 26% and 32%, respectively. In addition, we find that the gender gap in yield between male and female‐headed soybean‐producing households was small, with a yield gap of about 1%. However, we find a substantial gender gap in soybean net revenue, as the net revenue of female‐headed households was lower by about 20%, as compared to male‐headed households. Overall, our findings show that policymakers and their development partners can leverage varietal improvement to boost the yields of both male‐ and female‐headed households. However, closing the gender gap in crop income necessitates reducing the disparity in market linkages so that the female farmers can equally have better market access. Abstract : Field surveys were conducted to evaluate the impact of the adoption of improved soybean varieties in Northern Nigeria and the gender differences in impact. Results show that the adoption of improved soybean varieties by both male and female farmers significantly increased yield and net revenue. While there were no differences between male and female farmers in terms of yield, male farmers had significantly higher income than their female counterpart.